2018
DOI: 10.1073/pnas.1812932115
|View full text |Cite
|
Sign up to set email alerts
|

Axonal plasticity associated with perceptual learning in adult macaque primary visual cortex

Abstract: Perceptual learning is associated with changes in the functional properties of neurons even in primary sensory areas. In macaque monkeys trained to perform a contour detection task, we have observed changes in contour-related facilitation of neuronal responses in primary visual cortex that track their improvement in performance on a contour detection task. We have previously explored the anatomical substrate of experience-dependent changes in the visual cortex based on a retinal lesion model, where we find spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…This is supported by studies of primate dopamine receptor distribution that have found more pronounced receptor densities in temporal compared to primary visual cortex 39 . In contrast, other neuromodulatory systems with stronger innervation to early visual regions 40 may also play a role in VPL-related plasticity observed in these earlier regions 33,41 . The latter hypothesis requires further testing.…”
Section: Discussionmentioning
confidence: 95%
“…This is supported by studies of primate dopamine receptor distribution that have found more pronounced receptor densities in temporal compared to primary visual cortex 39 . In contrast, other neuromodulatory systems with stronger innervation to early visual regions 40 may also play a role in VPL-related plasticity observed in these earlier regions 33,41 . The latter hypothesis requires further testing.…”
Section: Discussionmentioning
confidence: 95%
“…Alternatively, heterogeneity 46 or regional variance between somatosensory and motor oligodendrocytes may play a role in this differential response. The role of sheath retraction throughout learning remains to be explored, though recent work suggests this may regulate conduction velocity 47,48 and allow for increased axonal branching [49][50][51] . Concurrent multi-color in vivo imaging of reach-specific neurons and myelin sheath dynamics in the context of learning will provide further information into how neurons and oligodendrocytes interact to facilitate the consolidation of neural circuits.…”
Section: Discussionmentioning
confidence: 99%
“…Importance of the intracortical horizontal afferents is further exemplified in a meticulously executed study on the behaving monkey: it has showed that dynamic changes, pruning and sprouting, of the horizontally projecting axon collaterals of pyramidal cells took place in conjunction with perceptual training which lasted up to 8 weeks (Van Kerkoerle, Marik, Meyer Zum Alten Borgloh, & Gilbert, 2018). The extent of collateral sprouting was correlated to the monkeys' learning scores.…”
Section: What Is Physiologically Disrupted Following Md?mentioning
confidence: 99%